Diseño de un generador de agua atmosférico alimentado por energía solar con una capacidad de producción de 30 litros de agua por día, para una vivienda promedio en el municipio de Uribia, La Guajira (2022)
This research project provides an alternative solution to water scarcity through the generation of water by condensation, since it proposes as a focus of research to determine the capacity, quantity and type of the components included in the atmospheric water generator. Therefore, a steam compression cooling cycle is proposed, which provides the required water flow. Initially, a market study was carried out to see which photovoltaic cell system was the most suitable to implement in this project. The different calculations that justify the selection of the system were made. This alternative is taken, since solar energy is one of the most promising types of clean energy in the municipality of Uribia, La Guajira. Then the equipment of the thermodynamic process that allows the water to be condensed from the atmosphere is chosen. This entire thermodynamic process is fed by the energy obtained from the photovoltaic cell system that has already been selected. The necessary components for the accumulation and filtration of water that allows its subsequent consumption are also chosen. Finally, the design of a structure that supports the thermodynamic circuit equipment and the water accumulation and filtration components is made.